Evidence in the museum: Curating a miscarriage of justice - Biber, Katherine (Theoretical criminology, 2018)
After the conclusion of criminal proceedings, criminal evidence sometimes survives in what is described here as an afterlife. In its afterlife, criminal evidence is preserved in various locations; this article explores the museum as a repository for evidentiary exhibits. It examines the case of Lindy Chamberlain, the victim of Australia's most notorious miscarriage of justice, and the evidence that has survived since her exoneration. Drawing upon interviews with Chamberlain herself, and also the curator of the Chamberlain collections at the National Museum of Australia, this article examines the challenges posed by curating a wrongful conviction.